A preliminary investigation of the properties of potassium magnesium phosphate cement-based grouts mixed with fly ash, water glass and bentonite. (20th March 2020) - Zhang, Yijie; Wang, Shugang; Zhang, Bo; Hou, Dongshuai; Li, Haiyan; Li, Liping; Wang, Jing; Lin, Chunjin
Highlights: Low-burned magnesium oxide is the auxiliary material of MPC, and the water-binder ratio is 1. Fresh-state properties of grouts with MPC, fly ash, bentonite and waterglass are studied. Mechanical properties and of grouts with MPC, FA, B and water class are studied. Combined effects of fly ash, bentonite and water glass are studied. Microstructure characteristics of MPC based grouts with FA and waterglass are presented. Abstract: Water inflow in a karst area has the characteristics of a large water volume and a fast flow rate, which makes the water inrush of a karst conduit flow extremely difficult to treat. Ordinary inorganic grouting materials have weak bonding with the interface, long initial and final setting time intervals and high loss rates of dynamic water filling. Phosphate cement has good interfacial bonding and instantaneous final setting after the initial setting, which is suitable for dynamic water conduit plugging. In this work, we developed anti-scouring grouts based on light-burned magnesia, potassium dihydrogen phosphate, Class F fly ash, water glass, and bentonite. A condensate based on potassium magnesium phosphate cement (MKPC) is formed using Class F fly ash (0–30%) to replace some of the MgO and KH2 PO4 . Then, the three materials form a cementitious material system. The water-cement ratio is 1:1 and is then modified with bentonite (5%) and water glass (0–6%). The basic properties of the grouts were studied by measuring the setting time, viscosity, compressive strength (after 3 d, 7 d, and 28 d), and flow distance. The microscopic properties of the hardened stone were studied by using both X-ray diffraction (XRD) and scanning electron microscope (SEM). The experiments show that the molar ratio of MgO to KH2 PO4 (M/P) along with the water glass and fly ash contents play a significant role in the setting time, compressive strength, and viscosity of the grouts. The addition of fly ash can reduce the fluidity of the grouts and the early strength; however, the 28-day compressive strength of the grouting material mixed with 30% class F fly ash is higher than that of the grouting material mixed with 10% and 20% Class F fly ash. Water glass can reduce the setting time and fluidity of the grouts and can increase the strength of the grouts.